Providing Economic Security of Enterprises as Precondition its Sustainable Development - Полозова, Т. В.; Журавель, М. Ю.; Фастова, Н. І. (Sp. z.o.o. «Nauka i studia», 2010)
Recommendations regarding the formation of complex scientific-based aproach to the system of economic security of enterprises were proposed. In this aproach, is should be taken into account all the possible economic interests of businesses that will ensure effective imlementation of corporate strategy.
Keywords: economic security of an enterprise; providing of an economic security; functional components of economic security